Pragmatic, prospective comparative effectiveness trial of carbon ion therapy, surgery, and proton therapy for the management of pelvic sarcomas (soft tissue/bone) involving the bone: the PROSPER study rationale and design - Hoppe, Bradford S.; Petersen, Ivy A.; Wilke, Benjamin K.; DeWees, Todd A.; Imai, Reiko; Hug, Eugen B.; Fiore, Maria Rosaria; Debus, Jürgen; Fossati, Piero; Yamada, Shigeru; Orlandi, Ester; Zhang, Qing; et al. (Cancers, 2023)
Surgical treatment of pelvic sarcoma involving the bone is the standard of care but is associated with several sequelae and reduced functional quality of life (QOL). Treatment with photon and proton radiotherapy is associated with relapse. Carbon ion radiotherapy (CIRT) may reduce both relapse rates and treatment sequelae. The PROSPER study is a tricontinental, nonrandomized, prospective, three-arm, pragmatic trial evaluating treatments of pelvic sarcoma involving the bone. Patients aged at least 15 years are eligible for inclusion. Participants must have an Eastern Cooperative Oncology Group Performance Status score of two or less, newly diagnosed disease, and histopathologic confirmation of pelvic chordoma, chondrosarcoma, osteosarcoma, Ewing sarcoma with bone involvement, rhabdomyosarcoma (RMS) with bone involvement, or non-RMS soft tissue sarcoma with bone involvement. Treatment arms include (1) CIRT (n = 30) delivered in Europe and Asia, (2) surgical treatment with or without adjuvant radiotherapy (n = 30), and (3) proton therapy (n = 30). Arms two and three will be conducted at Mayo Clinic campuses in Arizona, Florida, and Minnesota. The primary end point is to compare the 1-year change in functional QOL between CIRT and surgical treatment. Additional comparisons among the three arms will be made between treatment sequelae, local control, and other QOL measures.
Gesehen am 04.08.2023